Digital Valorisation of Cultural Memories: Three Case Studies in the Emilia-Romagna Region - Collina, Federica; Fabbri, Francesca (Mimesis Journal, 2024)
Cultural heritage serves as a medium through which a community represents itself. To effectively communicate its legacy, thoughtful reflection on the values to be conveyed is essential for its enhancement. In this context, digital media have supported the creation and visualization of semantic connections for several years. The article presents three projects based on distinct realities in Emilia-Romagna, each utilizing digital technologies to communicate and preserve heritage through compelling narratives. By leveraging various digital storytelling methodologies, these projects have successfully enhanced cultural heritage in close collaboration with their respective communities.